Dosis de guano de las islas en las características agronómicas y rendimiento de forraje Tithonia diversifolia botón de oro en Loreto, Perú- 2020 - Yahuarcani Cachique, Frank Harold (2022)
The research work was carried out at the National University of the Peruvian Amazon at the Faculty of Agronomy, a cattle workshop located in the community of Zungarococha in Iquitos and the work is titled DOSE OF GUANO FROM THE ISLANDS IN THE AGRONOMIC CHARACTERISTICS AND PERFORMANCE OF FORAGE Tithonia diversifolia GOLDEN BUTTON IN LORETO, PERU- 2020 ”. The evaluations were carried out 60 days after sowing with vegetative seed (cuttings), in plots of 3 m x 1.2 m (3.6 m2) and an experimental area of 170 m2. With a Random Complete Block Design (DBCA), with five treatments and four repetitions, the treatments under study were: T0 control (or tons of island guano / ha), T1 (1 tons of island guano / ha), T2 (2 tons of island guano / ha), T3 (3 tons of island guano / ha) and T4 (4 tons of island guano / ha), obtaining the following results: With the dose of 4 tons of Guano of Island / ha it was possible to increase plant height, green matter, dry matter,% of plant coverage. In this sense, it was shown that, at higher doses of island guano, the greater the influence on the agronomic characteristics of the forage Tithonia diversifolia. With T4 (4 tons of Guano de Isla / ha), the highest yields in green matter of 10.81 kg / plot and 30,025.00 kg / hectare were achieved 60 days after sowing under the agroclimatic conditions of the area.